2017
DOI: 10.18535/jmscr/v5i2.120
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in the Epidemiology of Pancreatitis in Rural Population: Study at a Tertiary Health Care Centre

Abstract: Introduction: Worldwide, over the last decade, yearly incidence of pancreatitis and related hospitalizations have increased [1] . Acute pancreatitis is the most common cause of GI related hospitalizations in the world, with more than 274,000 hospitalizations in 2012 [1] .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 24 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…This is due to the major etiological factor being alcohol and decreased nutrient absorption and deficiencies, along with probable disturbances in the meal due to alcohol intake. 1,3,5,15 Other anthropometric assessments of MUAC and TSF also showed lower values compared to the normal cut-off for Indians. Similar results were obtained in one of the studies conducted on nutritional assessment of CP versus tropical pancreatitis.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…This is due to the major etiological factor being alcohol and decreased nutrient absorption and deficiencies, along with probable disturbances in the meal due to alcohol intake. 1,3,5,15 Other anthropometric assessments of MUAC and TSF also showed lower values compared to the normal cut-off for Indians. Similar results were obtained in one of the studies conducted on nutritional assessment of CP versus tropical pancreatitis.…”
Section: Discussionmentioning
confidence: 95%
“… 8 Alcohol consumption and gallstone obstruction were the major etiology identified in this study, similar to two other Indian studies conducted in eastern Indian and in rural Indian populations. 1 , 4 Even though subjects were from the lower economic group, daily consumption of alcohol was observed. It was also observed that subjects from rural backgrounds had higher consumption of alcohol and smoking compared to the urban group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations